A study on faciomaxillary trauma in a tertiary care hospital: a prospective study - Sivamuthu, T. Chenthil (International Surgery Journal, 2018)
Background: Faciomaxillary injuries are increasing in incidence in Tirunelveli district due to the increasing number of vehicles on the street which are inadequate and due to assault. The common denominator in both these situations is alcohol abuse. This study aims to assess the incidence, causative factors and management options of Faciomaxillary trauma. Methods: Around 50 case of faciomaxillary injuries admitted in the Department of Plastic surgery, TVMCH were taken up for study. The cases were studied for age, sex, personal habits, mode of injury, associated injuries, involved bones and type of fracture, clinical features, treatment modalities, and complications. Results: Road Traffic Accident (RTA) was the most common cause. Males aged 20-30 were the most commonly involved. Alcohol abuse and Intoxication was the most common antecedent event. Associated head, limbs and chest injuries were common. Mandible was the commonest bone to be fractured followed by zygoma, maxilla and nasal bones. ORIF and IMF was the common surgery performed. Conclusions: Alcohol abuse is the leading cause of faciomaxillary injuries. Educating the public about the traffic rules and the ill effects of drunken driving will go a long way to prevent these injuries.